Glomus rugosae, a new arbuscular mycorrhizal species in Glomeraceae (phylum Glomeromycota) from maritime sand dunes of Poland and an ash pond of Czech Republic - Błaszkowski, Janusz; Zubek, Szymon; Milczarski, Paweł; Malinowski, Ryszard; Goto, Bruno Tomio; Niezgoda, Piotr (Phytotaxa, 2024)
Preliminary morphological analyzes of an isolate producing glomoid spores in culture and comparison of its 45S nuc rDNA sequences (= 18S-ITS-28S) with sequences available in GenBank suggested that this isolate is an undescribed arbuscular mycorrhizal fungus of the genus Glomus in the family Glomeraceae (phylum Glomeromycota). This suggestion was confirmed by phylogenetic analyzes with sequences of 45S and the largest subunit of RNA polymerase II (rpb1) gene that placed this isolate in an autonomous clade sister to that with Glomus macrocarpum, the type species of Glomus and Glomeromycota. In the field, this species, here named G. rugosae sp. nov., was associated with roots of Rosa rugosa, which inhabited the coastal dunes of the Hel Peninsula in northern Poland. In single-species cultures, G. rugosae formed typical vesicular-arbuscular mycorrhiza. Phylogenetic analyzes with 45S sequences of Glomus species and environmental sequences with a similarity of >96% to the 45S sequences of G. rugosae showed that G. rugosae was previously detected in the Czech Republic.